KORELASI MOTIVASI GURU TERHADAP PRESTASI BELAJAR SISWA DI MTsN 1 KOTABARU - Achmad Ruslan Afendi (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2011)
Achievement reached by someone depend on motivation owned by it. Gains strength motivation owned, increasingly serious and persistent of business to reach purpose, height would also achievement reached. There is three important element; (1) that motivation starts the happening of change of energi neurofisiologis in every man, (2) motivation is marked with taste appearance (feeling), affection of someone who is determining man behaviour, (3) motivation is marked with reaction of reach purpose. In the requirement of achievement theory,Â  affiliates, in command (need for power) in having responsibility and prestigious. Teacher and students have motivation and creative in solving problem. Teacher has motivation and creative to teach, student also has motivation and creative learning especially in solving problem.Â Keywords: Motivasi Guru, Prestasi Belajar Siswa